Research Progress on Multifunctional Cultivated Land Use - Chen, Weiwei; Lu, Nan (International Journal of Global Economics and Management, 2024)
As a scarce land resource, cultivated land is the foundation for human survival, and the core element of regional food security and sustainable development. The protection of cultivated land is the basis for the survival and development of the country. The research on multifunctional utilization of cultivated land is of great significance to improve the comprehensive utilization efficiency of cultivated land and promote the sustainable use of cultivated land. We used the literature research method and the summary and induction method to review the research on the multifunctional use of cultivated land. The results show that (1) There are three main types of classification systems for cultivated land multifunctional use, ecological classification system, demand classification system, comprehensive supply and demand classification system; (2) The evaluation indexes of multifunctional cultivated land use were mainly selected from production, life and ecological function. The entropy method, fuzzy analytic hierarchy process (FAHP) and other methods were used to determine the weight of the evaluation index. (3) The value accounting of cultivated land resources is mainly calculated from economic value, social value and ecological value. (4) The management of multifunctional cultivated land is based on the characteristics of cultivated land joint production and cultivated land multi-functionality, and internalizes the externalities through institutional design to guide the rational competition of cultivated land functional utilization.